LEARNING ASSESSMENT IN THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM - Kaharuddin (Teaching English as a Foreign Language Overseas Journal, 2024)
History learning includes three activities, namely planning, implementation and assessment. However, history teachers tend to be more concerned with planning and implementation, while the assessment aspect is considered less important. In the Kurikulum Merdeka, assessment is an activity that is as important as learning, even the official guidelines are entitled "Learning and Assessment Guidelines". This article aims to analyze how history learning is assessed in the implementation of the independent curriculum. The method used is literature study, namely analyzing books, articles, guidelines and regulations related to assessment and the Kurikulum Merdeka. Assessment in the Kurikulum Merdeka uses formative and summative assessments. Formative assessments are carried out at the beginning and middle of learning, while summative assessments are carried out at the end of learning. The purpose of formative assessment is to improve the quality of learning, while summative determines the student's final grade. History learning in the Kurikulum Merdeka has several strands or skills which are also elements of learning outcomes. In preparing a history learning assessment, the teacher first determines the skills/strands and learning objectives, then decides on the form and technique of the relevant instruments. Determination of assessments needs to look at student characteristics so that student-centered learning.